Children Who Use Communication Aids Instructing Peer and Adult Partners During Play-Based Activity. (2nd April 2016) - Batorowicz, Beata; Stadskleiv, Kristine; von Tetzchner, Stephen; Missiuna, Cheryl
Abstract: Little is known about how children with severe motor impairments who use communication aids provide instructions when given control over interaction. In this study, 35 children – 18 who used communication aids and 17 who used natural speech – were videotaped in play-based activities. Both groups successfully instructed partners to build replications of models the partners could not see. The results demonstrate that children using communication aids can also have an active role in play-based activities using language, but that their experience with activities may be limited and their instructions may take longer to give. The children who used natural speech provided more detailed instructions and were more successful in guiding their partners. Creating opportunities for active participation in play may be important for the development of communicative autonomy.